KONSEP KHALIFATULLAH DAN IMPLIKASIMYA TERHADAP PENDIDIKAN ISLAM PERSPEKTIF M. QURAISH SHIHAB - Mar’atul Azizah; Raini (CENDEKIA: Jurnal Studi Keislaman, 2018)
The concept of Khalifah according to M. Quraish Shihab is that the Caliph must conform to; (a). Yahduna bi Amrina, can take people to the destination in accordance with our instructions (Allah). (b) Aabidin (including Iqam Al-Shalah and Ita’ Al-Zakat), establishing a prayer is a picture of a good relationship with God, while performing zakat is a picture of harmonious relations with humans. (c) Yuuqinun (full of confidence). The caliph must be sure that he can protect, nurture and guide so that every human being reaches the goal of his creation. (d) Shabaru (patience and fortitude), which is patient in carrying out God's mandate in the form of responsibility to prosper the earth and its contents by carrying out its laws in human life on earth. (e) Basing and implementing education according to Islam originating from Al-quran and As-Sunnah in order to realize the whole Muslim person. Because in essence the ultimate goal of Islamic education is to form Insan Kamil with a pattern of piety. The implication of the concept of Khalifatullah according to M. Quraish Shihab on Islamic education namely Islamic education must pay attention to the preparation of the design of educational programs outlined in the curriculum. In the curriculum guided in the scope of oriented on three things, namely: The achievement of the goal hablum minallah (relationship with God), the achievement of the goal hablum minannas. (relationship with humans), Hablum minal ‘alam (relationship with nature). Where the curriculum must also pay attention to the objectives of Islamic education which includes four aspects, namely. (1) aspects of akidah (yatlu alaihim ayatihi) (2) aspects of cleansing and forming behavior with ahklak al-karimah (wayuzakkihim), (3) aspects of rationality and transformation of science (wa yu'allimuhum al-kitab), (4) psychomotor aspects (wa al-hikmah).